SEJARAH MASUKNYA CINA Dl BALl DAN PENGARUHNYA PADA BUDAYA BALl HINGGA SAAT INI - Ida Bagus Putu Prajna Yogi (Naditira Widya, 2008)
There is no doubt that Bali has a rich variety of beautiful cultural items. Where is the source of Balinese culture ? It is believed that local culture known as Bali Aga culture mixed with Indian culture via Majapahit to form Balinese culture. However, when the Balinese cultural items areÂ examined carefully, there are some items of Balinese cultures that seems do not belong to all of these culture above. What is other influence to Balinese culture ? I argue that ChineseÂ gave some influences to the formation of Balinese culture as evidenced from the use of Gina coin in the ceremony, some traditional dances with Chinese influences, chinese style architectures on some pura in Bali, and in the folklores